Essentials of Pedodontics - Tilakraj T.N.; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2003)
The subject of Pedodontia which is making tremendous advancement with each day has become a superspeciality today. This subject which encompasses practically all the branches of dentistry as applied to pediatric patients has become a vast but challenging branch. It has been an arduous and challenging task to provide a lot of valuable and comprehensive information to the dental students in pedodontics. Care has been taken to incorporate recent development and advanced technology in the field of pediatric dentistry.
Keywords: Pedodontics; Electronic books